2009
DOI: 10.1534/genetics.109.105379
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive Responses to Nitrogen Starvation in the Dominant Active Mutants of the Fission Yeast Rheb GTPase

Abstract: Rheb, a Ras-like small GTPase conserved from human to yeast, controls Tor kinase and plays a central role in the regulation of cell growth depending on extracellular conditions. Rhb1 (a fission yeast homolog of Rheb) regulates amino acid uptake as well as response to nitrogen starvation. In this study, we generated two mutants, rhb1-DA4 and rhb1-DA8, and characterized them genetically. The V17A mutation within the G1 box defined for the Ras-like GTPases was responsible for rhb1-DA4 and Q52R I76F within the swi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 42 publications
2
29
0
Order By: Relevance
“…5C), which correlates with the decrease in cat1 ϩ level (Fig. 3A) and with previous observations that demonstrated canavanine resistance of tor2 temperature-sensitive alleles (48). A slight additive defect in the uptake of arginine is observed in ⌬isp7 tor2-51 mutant cells, under either semipermissive or restrictive conditions (Fig.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…5C), which correlates with the decrease in cat1 ϩ level (Fig. 3A) and with previous observations that demonstrated canavanine resistance of tor2 temperature-sensitive alleles (48). A slight additive defect in the uptake of arginine is observed in ⌬isp7 tor2-51 mutant cells, under either semipermissive or restrictive conditions (Fig.…”
Section: Resultssupporting
confidence: 90%
“…However, the relationship between Gtr1/2 and TORC1 is complex. Thus, for example tor2-ts cells are canavanine resistant (48), while ⌬gtr1 and ⌬gtr2 cells are canavanine sensitive (53). Recently, it was suggested that Tor2 has opposing effects on Cat1 activity; thus, while the transcript of cat1 ϩ is positively regulated by Tor2, the localization of Cat1 at the plasma membrane is negatively regulated through endocytosis (53).…”
Section: Resultsmentioning
confidence: 99%
“…We confirmed that the expression of the tor2 + gene under its endogenous promoter from a multicopy plasmid suppressed canavanine resistance of tor2-287 mutant cells ( Figure 2B), indicating that canavanine resistance is due to the tor2 mutation. Consistently, Murai et al (2009) demonstrated that another Tor2 allele, the tor2-ts6 mutant, was resistant to canavanine.…”
Section: Mutation or Inhibition Of Tor2 Activity Leads To Canavanine mentioning
confidence: 63%
“…We confirmed that the expression of the tor2 + gene under its endogenous promoter from a multicopy plasmid suppressed canavanine resistance of tor2-287 mutant cells ( Figure 2B), indicating that canavanine resistance is due to the tor2 mutation. Consistently, Murai et al (2009) demonstrated that another Tor2 allele, the tor2-ts6 mutant, was resistant to canavanine.Next, we examined several tor2 point mutants in which the wild-type tor2 + gene was replaced with a mutation on its chromosomal locus. The tor2 L1310P and tor2 E2221K mutants have activating mutations , and the tor2 S1837E mutation has an inactivating mutation in the residue crucial for the binding between the FRB domain in TOR and the FKBP12-rapamycin complex (Nakashima et al 2010).…”
mentioning
confidence: 63%
“…, which have been identified as hyperactivating mutations in fission yeast (Murai et al, 2009;Urano et al, 2005), from the chromosomal rhb1 + locus. Phosphorylation of p27 in rhb1 V17A but not in the wild-type rhb1 + or rhb1 K120R was significantly resistant to nitrogen starvation, similar to that in tsc2 cells (Fig.…”
Section: K120rmentioning
confidence: 99%